Pre-injury Comorbidities Are Associated With Functional Impairment and Post-concussive Symptoms at 3- and 6-Months After Mild Traumatic Brain Injury: A TRACK-TBI Study - Yue, John K.; Cnossen, Maryse C.; Winkler, Ethan A.; Deng, Hansen; Phelps, Ryan R. L.; Coss, Nathan A.; Sharma, Sourabh; Robinson, Caitlin K.; Suen, Catherine G.; Vassar, Mary J.; Schnyer, David M.; Puccio, Ava M.; et al. (Frontiers in Neurology, 2019)
Introduction: Over 70% of traumatic brain injuries (TBI) are classified as mild (mTBI), which present heterogeneously. Associations between preinjury comorbidities and outcomes are not well-understood, and understanding their status as risk factors may improve mTBI management and prognostication. Methods: mTBI subjects (GCS 13-15) from TRACK-TBI Pilot completing 3- and 6-month functional (Glasgow Outcome Scale-Extended (GOSE)) and postconcussive outcomes (Acute Concussion Evaluation (ACE) physical/cognitive/sleep/emotional subdomains) were extracted. Preinjury comorbidities >10% incidence were included in regressions for functional disability (GOSE≤6) and postconcussive symptoms by subdomain. Odds ratios (OR) and mean differences (B) were reported. Significance was assessed at p<0.0083 (Bonferroni correction). Results: In 260 subjects sustaining blunt mTBI, mean age was 44.0-years and 70.4% were male. Baseline comorbidities >10% incidence included psychiatric-30.0%, cardiac (hypertension)-23.8%, cardiac (structural/valvular/ischemic)-20.4%, gastrointestinal-15.8%, pulmonary-15.0%, and headache/migraine-11.5%. At 3- and 6-months separately, 30.8% had GOSE≤6. At 3-months, psychiatric (GOSE≤6: OR=2.75, 95% CI [1.44-5.27]; ACE-physical: B=1.06 [0.38-1.73]; ACE-cognitive: B=0.72 [0.26-1.17]; ACE-sleep: B=0.46 [0.17-0.75]; ACE-emotional: B=0.64 [0.25-1.03]), headache/migraine (GOSE≤6: OR=4.10 [1.67-10.07]; ACE-sleep: B=0.57 [0.15-1.00]; ACE-emotional: B=0.92 [0.35-1.49]), and gastrointestinal history (ACE-physical: B=1.25 [0.41-2.10]) were multivariable predictors of worse outcomes. At 6-months, psychiatric (GOSE≤6: OR=2.57 [1.38-4.77]; ACE-physical: B=1.38 [0.68-2.09]; ACE-cognitive: B=0.74 [0.28-1.20]; ACE-sleep: B=0.51 [0.20-0.83]; ACE-emotional: B=0.93 [0.53-1.33]), and headache/migraine history (ACE-physical: B=1.81 [0.79-2.84]) predicted worse outcomes. Conclusions: Preinjury psychiatric and preinjury headache/migraine symptoms are risk factors for worse functional and postconcussive outcomes at 3- and 6-months post-mTBI. mTBI patients presenting to acute care should be evaluated for psychiatric and headache/migraine history, with lower thresholds for providing TBI education/resources, surveillance, and follow-up/referrals.